Reviewing the pressures to reform film censorship in Malaysia - Shuaib, Farid Sufian; Islam, Md. Zahidul (2015)
Malaysia adopts a film censorship system where a statutorily established film censorship board determine exclusion of offensive scene from a film and determine the rating of the film. There were persistent pressures to modify or revamp this censorship system but the alternative is unclear. In order to understand these pressures and consequently the kind of reform required it is pertinent to identify the pressures and to understand the demand from such pressures. This study constitutes a preliminary study of this question that relies on secondary sources to identify and understand the pressures and such sources include newspaper reports and journal articles. The research found pressures from several sectors such as economic and political. Several issues also provide the pressures such as human rights and technological advancement. The understanding of these pressures will enable a proper response and reform to be formulated.